Analysis On The Influence Of Different Fuel Combustion Hot Gases On The Combustor Casing - Lim, Ban Aik (Universiti Sains Malaysia, 2021)
In this modernized world, the aviation industry is growing drastically. Thus, much research is performed to improve aircraft performance. The most critical component to be designed is the gas turbine or specifically the combustor, as it needs to perform high-temperature combustion under a broad range of flight conditions. In order to study and optimize the performance of combustor, a computational method is called for. My project describes a simplified model of a combustor. The whole combustion chamber is modeled using SOLIDWORKS 2018. Subsequently, this project also presents a computational study of the flow field generated in the combustor and how that flow field convicts through the combustor. The fuels considered are Jet-A, Biodiesel, Camelina Bio-synthetic Paraffinic Kerosine (CSPK), and Ethanol. Another topic of interest is to perform the fluid-structure interaction (FSI) simulation to observe the effect of different fuels combustion on the mechanical properties of the combustor. All of these are simulated numerically through ANSYS 19.2 software. The result obtained show that the CSPK is the most optimized fuel. The results of FSI show that the structure deformation is small and negligible. Next, detectable plastic deformation occurs when the combustor is subjected to thermal stress, while plastic deformation is not notable when the combustor is subjected to pressure stress.